2022
DOI: 10.3390/agronomy12040933
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Water and Nitrogen Strategies to Improve Forage Oat Yield and Quality on the Tibetan Plateau Using APSIM

Abstract: There is a great need for improving oat forage production to increase forage supply and protect grassland ecosystems on the Tibetan Plateau. We conducted two field experiments and modeling work to investigate the responses of oat (Avena sativa L.) forage yield and N uptake to water and N applications, and to optimize the water and N scheduling under rainfed and irrigated conditions. The experiments were conducted in 2017 and 2018 at Jintai farm in the northeast of the Tibetan Plateau. Two N-applying rates of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Water availability is required for imbibition and activation of metabolic reactions, which regulate embryo development and seedling growth [ 52 ]. Seeds cannot reach the critical moisture threshold required for imbibition under osmotic stress conditions and thus fail to germinate [ 40 ]. In this respect, reduced germination could serve as a survival strategy for unpredictable and low precipitation conditions, which guarantees seed longevity within seedbank until sufficient moisture is available for seed germination [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water availability is required for imbibition and activation of metabolic reactions, which regulate embryo development and seedling growth [ 52 ]. Seeds cannot reach the critical moisture threshold required for imbibition under osmotic stress conditions and thus fail to germinate [ 40 ]. In this respect, reduced germination could serve as a survival strategy for unpredictable and low precipitation conditions, which guarantees seed longevity within seedbank until sufficient moisture is available for seed germination [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The seeds were placed at the soil surface which obtained the highest germination percentage, and the resultant powder of oat straw was spread on the soil surface at a rate equivalent to the specified levels of the treatments. The amount of oat residue (as straw mulch) used in this study was representative of the quantity of mulch levels after harvest found in irrigated and dry land farming systems in China [ 39 , 40 ]. The trials were incubated under constant temperatures of 25°C and 12 h light/ 12 h dark in the incubator, and generally the plot size was 380 L. Seedling emergence, i.e., when the cotyledon was visible above the soil surface, was counted daily for four weeks or until emergence no longer occurred.…”
Section: Methodsmentioning
confidence: 99%
“…These output variables were chosen as they represent important processes of key ecosystem services and disservices in crop production. We compared point estimates, cumulative values or average flows, but the model could also be used to compare differences in daily flows over years or specific periods, or to calculate N or water use efficiency, as done by Ma et al (2022). APSIM also provides information on different N forms and simulates daily rates of transformation between different N pools, which could be valuable when assessing measures to mitigate different N losses, or management of SCs as green manures.…”
Section: Using Apsim To Assess Ecosystem Service Delivery From Croppi...mentioning
confidence: 99%
“…In Tibetan Plateau, local communities support sown forage crops such as oat. Recently, oat forage production can be more than 10.7 t of dry matter/ha in the Tibetan plateau (Ma et al, 2022). However, about 70% of artificial pasture in Qinghai–Tibetan Plateau (QTP) is cultivated by oat forage to eliminate the seasonal imbalance between livestock and herbage production (Xu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%